The Role of Metacognitive Monitoring and Control in Overcoming Cognitive Overload during the Impasse Phase - Rika Wahyu Saputri; Surya Sari Faradiba; M. Mahmudi Prasetiyo (Universitas Sembilanbelas November Kolaka, 2026)
This study was motivated by the urgency of the phenomenon of cognitive overload, which often triggers a phase of impasse or mental block in students when solving contextual mathematics problems. This condition causes students to often rush to apply irrelevant calculation procedures without analyzing the structure of the problem, resulting in strategic failure. This study aims to describe in depth the dynamics of students' metacognition, particularly the monitoring and control functions, and to analyze the effectiveness of visualization strategies in reducing this cognitive load. The research method used is a qualitative approach with a descriptive-exploratory design. The research subjects included junior high school students who were tested on their ability to solve PISA-type questions. Data collection was carried out using the Think Aloud Protocol (TAP) technique to record students' mental processes and verbalizations in real time when they encountered a deadlock. Data analysis techniques were carried out systematically through the stages of verbal data transcription, data reduction, visual presentation, and conclusion drawing, which were validated through interview triangulation. The results showed that the monitoring of metacognitive function plays a vital role as an early detection mechanism that helps students recognize anomalies between their tentative answers and the logic of the problem. Furthermore, the control strategy through image visualization proved effective in reducing extraneous cognitive load, enabling students to transform abstract representations into concrete ones and find the turning point for solving the problem. In addition to improving cognitive accuracy, successfully overcoming this impasse phase simultaneously increases students' self-efficacy or self-confidence. These findings recommend the importance of integrating metacognitive interventions in learning to build students' mathematical resilience.